Processes in vertical-flow reed beds nitrification, oxygen transfer and soil clogging - Kayser, K (Water science and technology : a journal of the International Association on Water Pollution Research, 2005)
Vertical-flow reed beds (VF) with intermittent feeding are extremely reliable regarding aerobic processes. For a save operation with high nitrification rates and without soil clogging it is essential to preserve aerobic conditions in the filter. The challenge is to keep aerobic conditions in the filter without oversizing the system (economical aspects). It is very difficult to determine the current oxygen content in the filters because it ultimately results from complex interactions of a large number of different influencing parameters such as loading rate, degree of clogging, temperature, and hydraulic behaviour of the reed bed. To gain better knowledge of this complex system, different tests and examinations were carried out over several years. Focusing on the questions of identification and the description of conversion and transport processes (water/gas), a full-scale treatment plant under clogged and non-clogged conditions was investigated in detail. Additionally soil column test were carried out. The results make it possible to describe some of the processes and their interactions in the filter body. Recommendations for a safe and controlled operation can be derived